ANALYSIS OF THE IMPACT OF SOCIAL MEDIA MARKETING ON CONSUMER BUYING BEHAVIOR IN THE DIGITAL - Nadia Dwi Irmadiani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to analyze the impact of marketing via social media (social media marketing) on ​​consumer purchasing behavior in the digital era. Through a systematic literature study approach, this research examines various scientific sources such as journals, articles and books published in the last 5-10 years. The analysis results show that social media plays an important role in shaping consumer perceptions, increasing brand awareness, and influencing purchasing decisions through visual content, customer reviews, and user-generated content. In addition, the unique characteristics of each platform such as Instagram, TikTok, YouTube, and Facebook have different influences on marketing strategies and consumer responses. This research also found that emotional engagement, interactivity, and content credibility were key factors in driving purchases. However, there are also challenges such as algorithm changes, content competition and digital reputation crises that business players need to anticipate. By understanding these dynamics, companies can design more effective and adaptive digital marketing strategies to optimally reach and influence consumers in the digital realm.